CHANGES IN SOCIETY'S POLITICAL MENTALITY - Yusufjanov Zahidjan (American Journals Publishing, 2023)
This article examines the transformational processes of the political mentality of society. The transformational processes of the political mentality of the society determine the changes shown in the thinking, working, communication and ideas of the society about political affairs. These processes depend on the reasons that took place in the society during a certain period or for many years and influenced the political mentality of the society.
Keywords: State, society, management, political technology, management, discredit, political party, mentality.